Peningkatan Keterampilan Kepemimpinan OSIS melalui Pelatihan Interaktif di SMKN 1 Cibatu Purwakarta - Sulistyanto, Tri Hadi; Kusmana, Oman; Izzati, Nur; Ramadesa, Andes; Firdaus, Fattah (Sinesia : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve the leadership skills of students who serve as members of the student council (OSIS) at SMKN 1 Cibatu at Cibatu District, Purwakarta Regency. The background of this activity is based on the potenial development of reflective thinking, decision-making accuracy, and concentration among students in carrying out leadership roles. The method used combines community education through lectures and interactive training through interactive games involving 45 students as participants. The evaluation was conducted using pre-test and post-test to measure participants’ improvement. The results show a significant increase in all measured indicators, where reflective thinking improved from 10% to 100%, while decision-making accuracy and concentration increased from 30% to 100%. These findings indicate that the training method is effective in improving students’ cognitive and behavioral abilities, particularly in leadership aspects. Therefore, this activity provides a positive contribution to the development of students’ leadership capacity to support their roles in school organizations